Moving South: Late Pleistocene plant exploitation and the importance of palm in the Colombian Amazon (2021)
ABSTRACT: The role of plants in early human migrations across the globe has received little attention compared to big game hunting. Tropical forests in particular have been seen as a barrier for Late Pleistocene human dispersals due to perceived difficulties in obtaining sufficient subsistence resources. Archaeobotanical data from the Cerro Azul rock outcrop in the Colombian Amazon details Late Pleistocene plant exploitation providing insight into early human subsistence in the tropical forest. The dominance of palm taxa in the assemblage, dating from 12.5 ka BP, allows us to speculate on processes of ecological knowledge transfer and the identification of edible resources in a novel environment. Following the hypothesis of Martin Jones from his 2009 work, “Moving North: archaeobotanical evidence for plant diet in Middle and Upper Paleolithic Europe”, we contend that the instantly recognizable and economically useful palm family (Arecaceae) provided a “gateway” to the unknown resources of the Amazon forest.